Cellular and genetic mechanisms involved in the generation of protective and pathogenic immune responses in human Chagas disease - Walderez Ornelas Dutra; Cristiane Alves Silva Menezes; Fernanda Nobre Amaral Villani; Germano Carneiro da Costa; Alexandre Barcelos Morais da Silveira; Débora d'Ávila Reis; Kenneth J Gollob (Memorias do Instituto Oswaldo Cruz, 2009)
Perhaps one of the most intriguing aspects of human Chagas disease is the complex network of events that underlie the generation of protective versus pathogenic immune responses during the chronic phase of the disease. While most individuals do not develop patent disease, a large percentage may develop severe forms that eventually lead to death. Although many efforts have been devoted to deciphering these mechanisms, there is still much to be learned before we can fully understand the pathogenesis of Chagas disease. It is clear that the host's immune response is decisive in this process. While characteristics of the parasite influence the immune response, it is becoming evident that the host genetic background plays a fundamental role in the establishment of pathogenic versus protective responses. The involvement of three complex organisms, host, parasite and vector, is certainly one of the key aspects that calls for multidisciplinary approaches towards the understanding of Chagas disease. We believe that now, one hundred years after the discovery of Chagas disease, it is imperative to continue with highly interactive research in order to elucidate the immune response associated with disease evolution, which will be essential in designing prophylactic or therapeutic interventions.